2010
DOI: 10.1111/j.1474-9726.2010.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylated proteins are eliminated during reproduction in C. elegans

Abstract: Summary Oxidatively damaged proteins accumulate with age in many species (Stadtman (1992) Science257, 1220–1224). This means that damage must be reset at the time of reproduction. To visualize this resetting in the roundworm Caenorhabditis elegans, a novel immunofluorescence technique that allows the detection of carbonylated proteins in situ was developed. The application of this technique revealed that carbonylated proteins are eliminated during C. elegans reproduction. This purging occurs abruptly within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 48 publications
6
40
0
Order By: Relevance
“…This is in line with other studies, which demonstrate that the germline, like the soma, displays aging-related features, including increased oxidative damage (Goudeau & Aguilaniu, 2010). For example, the function of D. melanogaster germline stem cells declines upon aging, and this can, in part, be counteracted by overproduction of superoxide dismutase (Pan et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with other studies, which demonstrate that the germline, like the soma, displays aging-related features, including increased oxidative damage (Goudeau & Aguilaniu, 2010). For example, the function of D. melanogaster germline stem cells declines upon aging, and this can, in part, be counteracted by overproduction of superoxide dismutase (Pan et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…We measured the relative amount of carbonylated proteins which result from protein oxidation in emv(RNAi)- treated and tomm-40(RNAi) -treated larvae of similar ages (Figure 4C). The levels of carbonylated proteins in worms is an indirect measure of its redox status, since proteins that are oxidized become irreversibly carbonylated [34] and since the carbonylation status in worms is not reset until embryogenesis [35]. Using this assay we could detect no significant difference between lysates from emv(RNAi) and tomm-40(RNAi) animal.…”
Section: Resultsmentioning
confidence: 91%
“…Studies in C. elegans have suggested that damage-clearance mechanisms in the germline may prevent parental damage from being transmitted to progeny5. In the C. elegans hermaphrodite, germ cells form a developmental gradient, with mature oocytes located proximally, near the sperm (Fig.…”
mentioning
confidence: 99%
“…1a). Protein carbonylation, a form of oxidative damage, is high in immature distal germ cells, but decreases in sperm-proximal oocytes5. This decrease is likely to be signalled by sperm-derived ‘major sperm proteins’ (MSPs), which trigger meiotic maturation in nearby oocytes2,6 (Fig.…”
mentioning
confidence: 99%